Rapid Chemical Reaction Monitoring by Digital Microfluidics‐NMR: Proof of Principle Towards an Automated Synthetic Discovery Platform. (12th September 2019) - Wu, Bing; von der Ecken, Sebastian; Swyer, Ian; Li, Chunliang; Jenne, Amy; Vincent, Franck; Schmidig, Daniel; Kuehn, Till; Beck, Armin; Busse, Falko; Stronks, Henry; Soong, Ronald; et al.
Abstract: Microcoil nuclear magnetic resonance (NMR) has been interfaced with digital microfluidics (DMF) and is applied to monitor organic reactions in organic solvents as a proof of concept. DMF permits droplets to be moved and mixed inside the NMR spectrometer to initiate reactions while using sub‐microliter volumes of reagent, opening up the potential to follow the reactions of scarce or expensive reagents. By setting up the spectrometer shims on a reagent droplet, data acquisition can be started immediately upon droplet mixing and is only limited by the rate at which NMR data can be collected, allowing the monitoring of fast reactions. Here we report a cyclohexene carbonate hydrolysis in dimethylformamide and a Knoevenagel condensation in methanol/water. This is to our knowledge the first time rapid organic reactions in organic solvents have been monitored by high field DMF‐NMR. The study represents a key first step towards larger DMF‐NMR arrays that could in future serve as discovery platforms, where computer controlled DMF automates mixing/titration of chemical libraries and NMR is used to study the structures formed and kinetics in real time. Abstract : Automatisiertes Entdecken : Eine Kombination aus Kernspinresonanz (NMR) und digitaler Mikrofluidik (DMF) ermöglicht das Bewegen und Mischen von Submikroliter‐Volumina von Reagenzien innerhalb des NMR‐Spektrometers, um Reaktionen einzuleiten. Die Methode erlaubt die Überwachung von Reaktionen knapper oder teurer Reagenzien und eröffnet das Potenzial für zukünftige automatisierte synthetische Forschungsplattformen.